Effects of formoterol on endurance performance in athletes at an ambient temperature of -20° - Tjorhom, A.; Riiser, A.; Carlsen, K. H. (Scandinavian Journal of Medicine & Science in Sports, 2007)
The use of inhaled ß2-agonists is restricted in sports. No benefit of inhaled formoterol upon performance was found in healthy athletes under normal climatic conditions, but it has not been investigated whether formoterol improves performance in athletes during exposure to cold. To investigate the effect of inhaled formoterol vs placebo upon performance and lung function at -20°C in 20 healthy male athletes. We used a randomized double-blind, placebo-controlled, cross-over design. The subjects performed a run until exhaustion after inhaled study drug. The speed was 95% of the predetermined maximal oxygen uptake (O2 max) the first minute and increased to 107% of O2 max for the remaining part of the test. Time until exhaustion, ventilation (E), O2, respiratory rate (RR), tidal volume (VT), heart rate (HR) and arterial oxyhemoglobin saturation (SPO2) were recorded during exercise. Lung function was measured before inhaling, after inhaling the study drug and after the treadmill run. Inhaled formoterol did not improve endurance performance in cold environments compared with placebo, although formoterol significantly improved lung function (FEV1, FEF50 and PEF) and HR 4 min after the start of the exercise. Inhaled formoterol did not improve endurance performance in healthy, well-trained athletes exposed to cold.